Nommer les biens du Patrimoine mondial : processus de patrimonialisation et réinvention toponymique - Christophe Gauchon (EchoGéo, 2020)
Naming the World heritage and characterizing the outstanding universal value. The paper deals with the naming of World Heritage sites as they are listed by UNESCO, as a form of semantic production. The names of the 1123 inscribed sites in 2019 are here analyzed, and a first typology is submitted. Sometimes, the names of the inscribed sites are modified either during the application or several years after their inscription. These changes show the will of members states of individualizing their own heritage, using native languages or imaginative names. Then, the analysis of these names could be compared with the doctrinal texts published by Unesco about the significance of Outstanding universal value. How the selected names can take part in making the proof of this Outstanding universal value? In the whole list, many names can be found with historic, national or ethnic mentions which aim at specific character more than universality promoted by Unesco.